2010
DOI: 10.1186/1471-2458-10-265
|View full text |Cite
|
Sign up to set email alerts
|

Increasing uptake of colorectal cancer screening in Korea: a population-based study

Abstract: BackgroundColorectal cancer (CRC) screening rates are low in most Asian countries and remain largely unknown. This study examined trends in CRC screening rates after the introduction of the Korean National Cancer Screening Programme (NCSP) and determined the factors associated with uptake of CRC screening by test modality over time.MethodsAn annual population-based survey conducted through nationally representative random sampling from 2005-2008. In total, 3,699 participants from the 2005-2008 surveys were sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 25 publications
0
31
1
Order By: Relevance
“…Although these challenges appear substantial, they are not insurmountable, as demonstrated by the increase in CRC screening test participation in Korea as a result of health care policies and pubic awareness campaigns. 26 The respondents' ages differed considerably among countries and may have led to bias in the results of knowledge of CRC. Because previous studies demonstrated better knowledge in older people, the superior knowledge in countries such as Japan may have been attributable to their higher proportion of older respondents.…”
Section: Discussionmentioning
confidence: 99%
“…Although these challenges appear substantial, they are not insurmountable, as demonstrated by the increase in CRC screening test participation in Korea as a result of health care policies and pubic awareness campaigns. 26 The respondents' ages differed considerably among countries and may have led to bias in the results of knowledge of CRC. Because previous studies demonstrated better knowledge in older people, the superior knowledge in countries such as Japan may have been attributable to their higher proportion of older respondents.…”
Section: Discussionmentioning
confidence: 99%
“…The history of CRC screening in South Korea is relatively short compared to the US. In 2002, South Korea developed guidelines for CRC screening in average-risk adults, and the government introduced nationwide CRC screening as part of the National Cancer Screening Program (NCSP) in 2004 (Choi et al 2010). Currently, in Korea, both government-organized and opportunistic CRC screening is available.…”
Section: Introductionmentioning
confidence: 99%
“…CRC has been rapidly increasing in Asia, and Asian countries including China, Japan, Singapore, and Korea have recently witnessed two-to fourfold increases in its incidence [2,3]. The epidemiologic change in Asia indicates that CRC screening and population compliance are crucial to the success of the CRC screening program.…”
Section: Introductionmentioning
confidence: 97%